2011
DOI: 10.1088/0004-637x/730/1/24
|View full text |Cite
|
Sign up to set email alerts
|

POSSIBLE CHARGE-EXCHANGE X-RAY EMISSION IN THE CYGNUS LOOP DETECTED WITHSUZAKU

Abstract: X-ray spectroscopic measurements of the Cygnus Loop supernova remnant indicate that metal abundances throughout most of the remnant's rim are depleted to ∼0.2 times the solar value. However, recent X-ray studies have revealed in some narrow regions along the outermost rim anomalously "enhanced" abundances (up to ∼1 solar). The reason for these anomalous abundances is not understood. Here, we examine X-ray spectra in annular sectors covering nearly the entire rim of the Cygnus Loop using Suzaku (21 pointings) a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 75 publications
(108 reference statements)
4
79
0
Order By: Relevance
“…Radially both this analysis and that of Katsuda et al (2011) agree with the theoretical calcuations done by Lallement (2004), at least qualitatively. In that work, the author shows that CX effects are generally negligible for an SNR in the Sedov phase, except in the narrow rim region where line of sight effects amplify the fraction of emission from CX.…”
Section: Comparison With Previous Worksupporting
confidence: 88%
See 2 more Smart Citations
“…Radially both this analysis and that of Katsuda et al (2011) agree with the theoretical calcuations done by Lallement (2004), at least qualitatively. In that work, the author shows that CX effects are generally negligible for an SNR in the Sedov phase, except in the narrow rim region where line of sight effects amplify the fraction of emission from CX.…”
Section: Comparison With Previous Worksupporting
confidence: 88%
“…In that work, the author shows that CX effects are generally negligible for an SNR in the Sedov phase, except in the narrow rim region where line of sight effects amplify the fraction of emission from CX. In Figure 3 of that work, it is shown that CX can contribute over 50% of the X-ray emission immediately behind the shock and approximately 30% in the region contained within the shock radius(Rs) and r=0.98Rs (Katsuda et al 2011), thus detailing the confinement of CX to the rim. However, azimuthally we find that the regions with OVII Kα line centroid shifts do not match those with the emission enhancement at ∼ 0.7 keV, as studied by Katsuda et al (2011).…”
Section: Comparison With Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…There could be charge exchange (CX) emission contribution to that line complex, instead of a purely thermal emission. CX X-ray emission in SNRs has been detected in the Cygnus Loop and Puppis A remnants (Katsuda et al 2011(Katsuda et al , 2012. The fraction of CX to the X-ray emission can be enhanced if the hot gas is interacting with denser, neutral gas, as we suggest for MCSNR J0517−6759.…”
Section: Environmental Effects and Asymmetric Evolutionmentioning
confidence: 55%
“…In addition, X-ray emissions from certain regions along northeast and southwest limbs have relatively high metal abundances also suggesting a high-mass, core-collapse supernova (Tsunemi et al 2007;Katsuda et al 2008;Kimura et al 2009;Uchida et al 2009;Fujimoto et al 2011;Katsuda et al 2011). Hubble (1937) of the bright eastern and western nebulae away from the centre of expansion.…”
Section: Introductionmentioning
confidence: 99%